The Monday Effect: Evidence from Malaysian Stock Market - Tam, Kok Chian (2009)
The Monday effect has been identified by researchers in the 1920s. Past literatures have been well recorded that expected returns vary with the day of the week. It is well known as one of the most puzzling empirical findings in finance. This paper re-examines the Monday effect on the Malaysian equity market. There is evidence that the Monday negative returns has become to positive returns and is the highest among the rest of weekdays in developed markets. Harvey (1995) suggested that the Malaysian market is reasonably integrated with the developed capital market. Besides, this paper also examines the Monday effect on the sectoral indices, which will give a detailed picture of the stock market instead relying on the major composite indices. Returns of individual stocks are expected to be less statistically significant as compare of sectoral indices. This investigation on sectoral indices provides benefits to the investor which will give a clearer picture of which industry is outperformed or underperformance. Then following Jaffe, Westerfield, and Ma (1989), this paper test whether Monday returns are determined by market conditions during the previous week. If Monday returns are correlated with returns of previous week, they are predictable and not random, thus violating the weak form of Efficient Market Hypothesis. This investigation also applies to the stock indices and the sectoral indices as well. This gives clearer picture to the investor on the condition of the stock market in Malaysia.